2015
DOI: 10.3803/enm.2015.30.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Profile of Well-Differentiated Thyroid Cancer in Asians

Abstract: Recent advances in molecular diagnostics have led to significant insights into the genetic basis of thyroid tumorigenesis. Among the mutations commonly seen in thyroid cancers, the vast majority are associated with the mitogen-activated protein kinase pathway. B-Raf proto-oncogene (BRAF) mutations are the most common mutations observed in papillary thyroid cancers (PTCs), followed by RET/PTC rearrangements and RAS mutations, while follicular thyroid cancers are more likely to harbor RAS mutations or PAX8/perox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
74
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 92 publications
6
74
0
1
Order By: Relevance
“…There have been studies showing that the prevalence of TERT mutation varies significantly among different countries, ranging from 4.1% to 25.5% for PTC (21)(22)(23)(24) and from 5.9% to 36.4% for follicular thyroid cancer (13,23). Among these data, the prevalence in China was reported to be 4.1%-11.3% for PTC (13,21,24), relatively lower than in western countries.…”
Section: Discussionmentioning
confidence: 99%
“…There have been studies showing that the prevalence of TERT mutation varies significantly among different countries, ranging from 4.1% to 25.5% for PTC (21)(22)(23)(24) and from 5.9% to 36.4% for follicular thyroid cancer (13,23). Among these data, the prevalence in China was reported to be 4.1%-11.3% for PTC (13,21,24), relatively lower than in western countries.…”
Section: Discussionmentioning
confidence: 99%
“…PPAR pathway was composed by a group of nuclear receptors which played pivotal roles in cellular differentiation, development and lipid metabolism [35]. The abnormal activation of the signal way implicated with tumorigenesis of bladder cancer, esophageal cancer, follicular thyroid cancers, etc [36][37][38]. In this study, we found that PPAR signal pathway was involved in the progression of PTC.…”
Section: Cellular Physiologymentioning
confidence: 57%
“…13 Musholt et al 14 considered that mutations of RET/PTC, RAS, and PAX8/peroxisome proliferator-activated receptor ␥ (PPAR␥) were predominantly associated with thyroid malignancy with varying frequency and had less impact on the clinical management. However, in the study of Song et al, 15 BRAF mutations were the most common ones observed in PTCs, followed by RET/PTC rearrangements and RAS mutations, while follicular thyroid cancers were more likely to have RAS mutations or PAX8/PPAR␥ rearrangements. 15 Therefore, more extensive research is needed in genetic testing.…”
mentioning
confidence: 85%
“…However, in the study of Song et al, 15 BRAF mutations were the most common ones observed in PTCs, followed by RET/PTC rearrangements and RAS mutations, while follicular thyroid cancers were more likely to have RAS mutations or PAX8/PPAR␥ rearrangements. 15 Therefore, more extensive research is needed in genetic testing.…”
mentioning
confidence: 85%